Atherosclerotic Coronary Plaque features in patients with Acute Coronary Syndrome and Chronic Obstructive Pulmonary Disease. (3rd October 2022) - Russo, M; Camilli, M; La Vecchia, G; Caffe', A; Iannaccone, G; Rinaldi, R; Del Buono, M; Trani, C; Liuzzo, G; Crea, F; Montone, R A
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a common respiratory disorder characterized by airflow limitation, persistent respiratory symptoms and chronic lung inflammation. Previous studies reported a robust relationship between COPD and coronary artery disease (CAD). Local and systemic inflammation, known to play a role in atherosclerosis development, has been reported in patients with COPD, and has been proposed as one of the possible pathogenetic factors linking COPD and CAD. However, data on atherosclerotic coronary pattern and coronary inflammation in COPD patients are lacking. Purpose: To study the characteristics of atherosclerotic coronary plaques and local inflammation by using optical coherence tomography (OCT) in COPD patients presenting with acute coronary syndromes (ACS). Methods: ACS patients undergoing intracoronary OCT imaging of the culprit vessel were retrospectively identified. Coronary plaque characteristics and OCT-defined macrophage infiltration (MØI) were assessed by OCT. ACS patients were divided into 2 groups according to the presence or the absence of an established diagnosis of COPD, and coronary plaque features and MØI both at the culprit plaque site and along the culprit vessel were compared between the two groups. Results: Among 146 ACS patients (mean age, 66, 1±12, 7 years, 109 males), 47 (32, 2%) had COPD. Patients with COPD were older, were more frequently on therapy with an angiotensin receptor blocker, had lower hemoglobin, total cholesterol and triglycerides levels, and had higher serum creatinine levels. The prevalence of different mechanisms of ACS were similar between COPD and noCOPD patients (plaque rupture: 57, 4% vs. 45, 4%, plaque erosion: 23, 4% vs. 32, 3%, calcified plaque: 19, 1% vs. 22, 2%, respectively, overall p=0, 381). OCT analysis of plaque microstructures showed that COPD patients had significantly higher prevalence of MØI (78, 7% vs. 54, 4%, p=0, 005), thin cap fibroatheroma (TCFA) (48, 9% vs. 22, 2%, p=0, 001), spotty calcium (68, 1% vs. 26, 3%, p<0, 001) and calcifications (83, 0% vs. 66, 7%, p=0, 040) at the culprit site than noCOPD patients. In the multivariate logistic regression analysis performed to adjust for clinical features, COPD was independently associated with MØI both at the culprit site (OR: 4, 726, CI: 1, 599; 13, 971, p=0, 005) and along the culprit vessel (OR: 2, 193, CI: 1, 110; 4, 332, p=0, 024). Similarly, COPD was independently associated with the presence of TCFA both at the culprit site (OR: 5, 737, CI: 1, 877; 17, 540, p=0, 002) and along the culprit vessel (OR: 2, 796, CI: 1, 408; 5, 553, p=0, 003). Conclusions: In ACS patients undergoing OCT imaging of the culprit vessel, COPD was an independent predictor of local plaque inflammation and plaque vulnerability both at the culprit site and along the culprit vessel. Our results may suggest that a higher inflammatory milieu in COPD patients might enhance local coronary inflammation, promoting CAD development and plaque vulnerability. Funding Acknowledgement: Type of funding sources: None.